Physical and nutritional quality of retails cakes of Dhaka city - Begum, F; Sarker, AK; Ahmed, S; Mondal, K; Anjum, S (Bangladesh Journal of Scientific and Industrial Research, 2016)
The nutrient content and other quality parameters of retails cake samples collected from different markets of Dhaka city was evaluated. Irrespective of the brand or types of cake analyzed, none of the 13 retails cakes samples were found comply with BSTI standard weight and on an average, 5-10g less-weight was observed compared to the labeled weight. The moisture content was found within the BSTI acceptable level. The protein content (crude) ranging from 4.3% to 6.5% was observed, indicating that the cakes were prepared using flour containing low protein that gives softness to the cakes. On the other hand, negligible amount of fiber contents (0.007 - 0.244 %) was observed indicated that no effect on protein digestibility by pepsin and also absorption of fats. However, acid values (AV) of five cake samples were within the acceptable range (0.69 - 1.00 mg KOH/100g) of BSTI standard and the remaining eight samples were found higher (1.07-4.75 mg KOH/100g) than the acceptable limit. The peroxide values were found higher (20.27-49.4 mEq/kg) in all thirteen cake samples analyzed, indicated that all fats were in rancid condition. The iodine values (62.18-120.22) of extracted fats were low which indicates saturated nature of fats. The acid insoluble ashes of eight cake samples were higher than the permissible limit (0.1%) compared to BSTI standard. Metal content (sodium, calcium) and trace metal (iron) contents was found in the range of 24.43 - 149.15 mg/100g; 32.59 - 69.70 mg/100g and 0.96 - 8.18 mg/100g, respectively, which is higher than the BSTI standard. Therefore, the retails cake samples analyzed was of both good and poor quality. Bangladesh J. Sci. Ind. Res. 51(1), 35-40, 2016